Three-component heteroannulation for tetrasubstituted furan construction enabled by successive defluorination and dual sulfonylation relay. Issue 2 (11th January 2021) - Cai, Song-Zhou; Ge, Danhua; Sun, Li-Wen; Rao, Weidong; Wang, Xin; Shen, Zhi-Liang; Chu, Xue-Qiang
Abstract : An efficient method for the facile assembly of fluoroalkylated tetrasubstituted furan derivatives via a three-component cascade reaction of polyfluoroalkyl peroxide with sulfinates was developed. Abstract : Synthetic strategies by making use of one-pot multi-step cascade reactions are of special interest. Herein, an efficient three-component tandem reaction of polyfluoroalkyl peroxides with sulfinates for the facile construction of fluoroalkylated tetrasubstituted furan derivatives has been developed. The combination of DABCO and Cs2 CO3 was found to be essential for the success of the reaction. This modular and regioselective approach proceeded via an unprecedented sequence of successive defluorination, dual sulfonylation, and annulation relay, along with four C(sp 3 )–F bonds cleaved and two new C–S bonds formed. In addition, this transition metal-free C–F bond functionalization which is amenable to gram-scale synthesis occurred under mild reaction conditions and has broad substrate scope and excellent functional group tolerance. Moreover, this defluorinative protocol also enabled the late-stage functionalization of complex compounds, which could potentially find synthetic utility in drug discovery.